Deskripsi Kemampuan Pemahaman Matematis Siswa SMP Berdasarkan Teori APOS - Mahfuziah Rusfiana; Ramlah Ramlah; Haerudin Haerudin (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2020)
This study aims to describe the mathematical understanding of junior high school students on quadrilateral based on the APOS theory. This study used a qualitative approach to the case study method with the subject as many as 3 students of class VII of one of the State Junior High Schools in Karawang district, using a test question description of comprehension and interview abilities. Data analysis in this study was carried out with data reduction, display data, and conclusion drawing or verification. Based on the results of data analysis, students with high abilities are able to meet the APOS stages on the indicators of presenting concepts in various forms of mathematical representations and developing necessary or sufficient requirements of a concept. Students with moderate abilities are able to meet the APOS stage on the indicators of presenting concepts in various forms of mathematical representations. And students with low abilities have not been able to meet the APOS stages on the four indicators. So, the students' mathematical understanding ability based on the APOS theory on the rectangular material is still low, where students have not been able to meet all the indicators of understanding based on the APOS theory.